Indigeneity in real time : the digital making of Oaxacalifornia - Kummels, Ingrid (Latinidad., 2023)
"Long before the COVID-19 crisis, Mexican Indigenous peoples were faced with organizing their lives from afar, between villages in the Oaxacan Sierra Norte and the urban districts of Los Angeles, as a result of unauthorized migration and the restrictive border between Mexico and the United States. By launching cutting-edge Internet radio stations and multimedia platforms and engaging as community influencers, Zapotec and Ayuujk peoples paved their own paths to a transnational lifeway during the Trump era. This meant adapting digital technology to their needs, setting up their own infrastructure, and designing new digital formats for re-organizing community life in all its facets-including illness, death and mourning, collective celebrations, sport tournaments, and political meetings-across vast distances. Author Ingrid Kummels shows how mediamakers and users in the Sierra Norte villages and in Los Angeles created a transborder media space and aligned time regimes. By networking from multiple places, they put into practice a communal way of life called Comunalidad and an indigenized American Dream-in real time"--